The availability of contraceptive methods in Turkish pharmacies and the status of pharmacies and pharmacists as providers of contraception - ÖZAYDIN, AYŞE NİLÜFER (TAYLOR & FRANCIS LTD, 2020)
Objectives We aimed to assess pharmacists' contraceptive knowledge and evaluate the contraceptives requested and sold in pharmacies. Methods A descriptive study was carried out in October 2016 in cooperation with the Chamber of Pharmacists of Istanbul Province, Turkey. Data were collected by questionnaire, and pharmacists' total knowledge scores were calculated. Results The study comprised 101 participants, 86.1% of whom were women. Combined oral contraceptives were the most requested (97.0%) and supplied (94.1%) contraceptive method. The mean total knowledge score of pharmacists was 51.6 +/- 12.9 (median 54.0, range 14.0-72.0). Among pharmacists, 51.5% said they had never received any training about contraception. Conclusion The results showed that pharmacists providing contraceptive counselling services need continuing in-service training. The current regulations on the duties and responsibilities of pharmacists in Turkey involve the provision of counselling about medication use. Effective training is suggested to provide better quality services in family planning/reproductive health care.
Keywords: Counselling; family planning methods; fertility regulation; knowledge; pharmacist; EMERGENCY CONTRACEPTION; KNOWLEDGE; ATTITUDES; ACCESS